Reconstruction and dissection of the entire human visual pathway using diffusion tensor MRI - Hofer, Sabine; Karaus, Alexander; Frahm, Jens (Frontiers in Neuroanatomy, 2010)
The human visual system comprises elongated fiber pathways that represent a serious challenge for diffusion tensor imaging (DTI) and fiber tractography: while tracking of frontal fiber bundles may be compromised by the nearby presence of air-filled cavities, nerves, and eye muscles, the anatomic courses of the three main fiber bundles of the optic radiation are subject to pronounced inter-subject variability. Here, tractography of the entire visual pathway was achieved in six healthy subjects at high spatial accuracy, that is, at 1.8 mm isotropic spatial resolution, without susceptibility-induced distortions, and in direct correspondence to anatomic MRI structures. Using a newly developed diffusion-weighted single-shot STEAM MRI sequence, we were able to track the thin optic nerve including the nasal optic nerve fibers, which cross the optic chiasm, and to dissect the optic radiation into the anterior ventral bundle (Meyer's loop), the central bundle, and the dorsal bundle. Apart from scientific applications these results in single subjects promise advances in the planning of neurosurgical procedures to avoid unnecessary damage to the visual fiber system.